2015
DOI: 10.1089/ten.tea.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Microencapsulated Insulin-Secreting Cells Increase Keratinocyte Migration, Epidermal Thickness, Collagen Fiber Density, and Wound Closure in a Diabetic Mouse Model of Wound Healing

Abstract: Wound healing is a hierarchical process of intracellular and intercellular signaling. Insulin is a potent chemoattractant and mitogen for cells involved in wound healing. Insulin's potential to promote keratinocyte growth and stimulate collagen synthesis in fibroblasts is well described. However, there currently lacks an appropriate delivery mechanism capable of consistently supplying a wound environment with insulin; current approaches require repeated applications of insulin, which increase the chances of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Granular hydrogels comprise an agglomeration of hydrogel microparticles in a packed state, where the packing can either be loose to retain porosity between particles or in a highly jammed state to restrict particle movement. 163 The physical interactions between particles in granular systems lead to shear-thinning behavior that permits injectability without introduction of chemical modification or secondary inter-particle crosslinking to alter The injectable characteristics of granular hydrogels have been exploited in various biomedical applications including 3D scaffolds, [164][165][166][167] tissue repair, 19,[168][169][170] and local drug 18,171 and growth factor 172,173 delivery. Self-healing granular hydrogels comprised of HA-based hydrogel microparticles have been generated based on guest-host interlinking chemistry.…”
Section: Granular Hydrogelsmentioning
confidence: 99%
“…Granular hydrogels comprise an agglomeration of hydrogel microparticles in a packed state, where the packing can either be loose to retain porosity between particles or in a highly jammed state to restrict particle movement. 163 The physical interactions between particles in granular systems lead to shear-thinning behavior that permits injectability without introduction of chemical modification or secondary inter-particle crosslinking to alter The injectable characteristics of granular hydrogels have been exploited in various biomedical applications including 3D scaffolds, [164][165][166][167] tissue repair, 19,[168][169][170] and local drug 18,171 and growth factor 172,173 delivery. Self-healing granular hydrogels comprised of HA-based hydrogel microparticles have been generated based on guest-host interlinking chemistry.…”
Section: Granular Hydrogelsmentioning
confidence: 99%
“…Hydrogel precursor solution was prepared as previously described (Aijaz et al 2015). For molecular weight studies, a prepolymer solution containing 10% (w/v) PEGDA (3.4, 5, 10, or 20 kDa; Laysan Bio, Arab, AL), 1.5% (v/v) triethanolamine, 10% (w/v) pluronic F68, 37 mM 1-vinyl-2-pyrrolidinone, and 1.0 mM eosin Y was prepared in HEPES buffered saline (HBS, pH 7.4).…”
Section: Microsphere Formationmentioning
confidence: 99%
“…PEG has been used to encapsulate cells in macroscopic structures and in microscopic structures. Cells have been encapsulated within PEG microcylinders, microcapsules, microspheres, and conformal coats that have been formed using photolithography, microfluidics, emulsion, photopolymerisation, electrohydrodynamic sprays, and combinations of PEG and other materials (Cruise et al 1998, Uteza et al 1999, Koh et al 2002, Yeh et al 2006, Lu et al 2007, Wilson et al 2008, Teramura and Iwata 2009, Liu et al 2010, Olabisi et al 2010, Mahou et al 2012, Aijaz et al 2015, Olabisi 2015, Qayyum et al 2017. These PEG-encapsulated cells have been used for blood replacement, diabetes treatment, tissue engineering, fracture repair, and hormone replacement.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of stem cell research, stem cells could be differentiated to insulin-producing cells (66), which could be used as a new cell source for pancreatic tissue engineering. Interestingly, it has been recently demonstrated that hydrogel microencapsulated insulin-secreting cells can accelerate wound healing in a diabetic mouse model (67). …”
Section: Current Applications Of Bioencapsulation Technologies In Tismentioning
confidence: 99%